277 CESAREAN DELIVERY ASSOCIATED WITH SURVIVAL ADVANTAGE IN PRETERM SMALL FOR GESTATIONAL AGE INFANTS, USA, 1999-2000. (1st January 2006) - Lee, H. C.; Gould, J. B.
Abstract : Purpose: The benefit that breech preterm infants receive from cesarean delivery (CD) has not been as well established for vertex infants. Preterm intrauterine growth restricted fetuses, with placental insufficiency and less tolerance for labor, may benefit from CD. We compared gestational age (GA) specific neonatal mortality between vaginal and CDs for vertex small for GA (SGA) preterm infants in a national cohort. Methods: We analyzed the National Center for Health Statistics US Linked Birth/Death records, years 1999-2000, looking at 7, 694 live vertex singletons without lethal congenital anomaly born at 26 to 32 weeks GA to mothers without previous cesarean, with weight < 10th percentile for GA. We compared 28-day mortality rates for vaginal and CDs by GA and calculated crude relative risks (RR). We then assessed mortality by mode of delivery using a multivariable logistic regression model controlling for demographic factors (maternal race, ethnicity, education, age, and adequacy of prenatal care) and complications of pregnancy and labor associated with mortality (diabetes, incompetent cervix, preterm rupture, uterine bleeding, fever, previous preterm/SGA birth, excessive bleeding, maternal hypertensive disease). Results: 63% of preterm vertex SGA infants were delivered by cesarean. CD was associated with a significant survival advantage for GA 26-31 weeks and a trend toward benefit of cesarean at 32 weeks that was not statistically significant. The multivariable logistic regression model included sociodemographic factors as well as medical factors associated with mortality. Adjusting for these factors, the odds ratio of death associated with cesarean was 0.46 (95% CI 0.39, 0.54). Conclusions: Mortality at 28 days was reduced in preterm SGA vertex infants delivered by cesarean compared to vaginal delivery. This survival advantage persisted, with 54% reduction in mortality, after adjusting for social and other medical factors.